Psychological burden and quality of life in newly diagnosed inflammatory bowel disease patients - Bernabeu, Purificación; Belén-Galipienso, Olivia; van-der Hofstadt, Carlos; Gutiérrez, Ana; Madero-Velázquez, Lucía; García del Castillo, Gloria; García-Sepulcre, Mariana-Fe; Aguas, Mariam; Zapater, Pedro; Rodríguez-Marín, Jesús; Ruiz-Cantero, María-Teresa; Cameo, José I.; et al. (Frontiers in Psychology, 2024)
Objective Psychological factors, such as stress, anxiety, and depression, are frequently related to inflammatory bowel disease (IBD). However, few studies have examined these factors in patients newly diagnosed with IBD. The aim of the present study was to test the psychological burden in patients with a recent diagnosis of IBD and the factors related to this psychological burden. Methods We performed a prospective, multi-center, observational study in patients with a new diagnosis of IBD (≤6 months). The patients were recruited from four different Spanish hospitals. Clinical and demographic characteristics were collected. Patients were evaluated using the Hospital Anxiety and Depression Scale and quality of life questionnaire for patients with inflammatory bowel disease (IBDQ-32). The Scale of Stress Perceived by the Disease was used to assess stressful life events. Results We included 156 patients newly diagnosed with IBD [69 women; 80 Crohn’s disease (CD) and 76 ulcerative colitis (UC)], with a mean age of 42.3 (SD 16.21) years. A total of 37.2% of patients had symptoms of anxiety and 17.3% had symptoms of depression. Quality of life was affected in 30.1% of patients. Factors related to anxiety in early IBD were being a woman and having CD. The only factor related to depression was the presence of comorbidity. Being a woman and having suffered previous stressful life events were factors related to impaired quality of life. Conclusion Anxiety, depression, and impaired quality of life are frequent in patients with a recent diagnosis of IBD. This psychological burden is greater in women.